Crosstalk between ferroptosis and autophagy: broaden horizons of cancer therapy - Xingyu Liu; Halahati Tuerxun; Yixin Zhao; Yawen Li; Shuhui Wen; Xi Li; Yuguang Zhao (Journal of Translational Medicine)
Abstract Ferroptosis and autophagy are two main forms of regulated cell death (RCD). Ferroptosis is a newly identified RCD driven by iron accumulation and lipid peroxidation. Autophagy is a self-degradation system through membrane rearrangement. Autophagy regulates the metabolic balance between synthesis, degradation and reutilization of cellular substances to maintain intracellular homeostasis. Numerous studies have demonstrated that both ferroptosis and autophagy play important roles in cancer pathogenesis and cancer therapy. We also found that there are intricate connections between ferroptosis and autophagy. In this article, we tried to clarify how different kinds of autophagy participate in the process of ferroptosis and sort out the common regulatory pathways between ferroptosis and autophagy in cancer. By exploring the complex crosstalk between ferroptosis and autophagy, we hope to broaden horizons of cancer therapy.